2017
DOI: 10.1503/jpn.170060
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, psychiatric illness and the brain

Abstract: Tobacco smoking remains a leading cause of mortality and morbidity despite recent declines in prevalence. In 2012, global prevalence rates for tobacco smoking were estimated to be 31% for men and 6% for women.1 Rates of smoking are markedly higher among people with psychiatric illness than in the general population, estimated at being 2-5 times higher in patients with several disorders, including schizophrenia, mood disorders, anxiety disorders, attentiondeficit/hyperactivity disorder (ADHD), binge eating diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 34 publications
0
33
0
1
Order By: Relevance
“…Our findings add evidence to previous research and treatment guidelines, which suggest that targeting physical activity might reduce the burden associated with depressive disorders. 28 Smoking is associated with adverse changes in brain structure and neural circuity in the brain regions implicated in many mental disorders 29 and with neuroadaptations in the nicotinic pathways in the brain, which manifest as depressed mood, agitation, and anxiety shortly after a cigarette is smoked. 30 Despite these plausible mechanisms, a mendelian randomisation study 31 suggested that the link between smoking and depression might not be causal.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings add evidence to previous research and treatment guidelines, which suggest that targeting physical activity might reduce the burden associated with depressive disorders. 28 Smoking is associated with adverse changes in brain structure and neural circuity in the brain regions implicated in many mental disorders 29 and with neuroadaptations in the nicotinic pathways in the brain, which manifest as depressed mood, agitation, and anxiety shortly after a cigarette is smoked. 30 Despite these plausible mechanisms, a mendelian randomisation study 31 suggested that the link between smoking and depression might not be causal.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, 23.8 % of adults in Germany smoked (daily or occasionally) [24]. However, rates of smoking among patients with mental illnesses are 2-5 times higher than in the general population [25], explaining the observed percentage in our study. In Germany in 2015, the prevalence of lowrisk alcohol consumption was 56.4 % and of high-risk consumption 15.2 % [26].…”
Section: Discussionmentioning
confidence: 52%
“…The second important independent predictor of PD was smoking. According to Boksa, smoking acts as (a) a causal factor of some mental disorders, (b) a factor modulating presentations of mental disorders, and (c) as a factor modulating progression and medications of mental disorders (Boksa, ). Our results went in line with Choi et al’s study, who experimentally found that smoking might relieve physiological and psychological responses to stress (Choi, Ota, & Watanuki, ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Boksa, smoking acts as (a) a causal factor of some mental disorders, (b) a factor modulating presentations of mental disorders, and (c) as a factor modulating progression and medications of mental disorders (Boksa, 2017 the other hand, several studies reported that smoking was positively associated with PD (Choi, Chan, & Lehto, 2018;Zvolensky et al, 2018).…”
Section: Discussionmentioning
confidence: 99%